Análise comparativa in vitro da citotoxicidade dos ácidos hialurônicos de alto e baixo peso molecular em enxertia óssea - Bordin, Thaisa Barizan (2014)
In recent decades, tissue engineering techniques have been reported in the literature as an alternative to conventional autogenous grafts for bone defects and subsequent installation of dental implants, combining a material with the same biological properties of autogenous bone without its limiting factors. This technology requires a carrier for the cells, where hyaluronic acid, a natural glycosaminoglycan, appears to have suitable characteristics to carry out this role. It exerts various biological functions depending on its molecular weight, which can be classified as high (> 1000 kDa), low (from 50 to 1000 kDa) or very low (<50 kDa). Furthermore, there is the hyaluronidase, an enzyme that degrades hyaluronic acid into smaller fragments, influencing the cellular response. Thus, this study aimed to evaluate in vitro the influence of the enzyme hyaluronidase (HYAL) on the high hyaluronic acid (HA-HMW) and low molecular weight (HA-LMW) and their potential cytotoxicity on NIH - 3T3 cells. The MTT assay was performed analyzing cell viability of the following groups: (G1) Cells + HA-HMW; (G2) Cells + HA- LMW; (G3) Cells + HA-HMW + HYAL; (G4) Cells + HA-LMW + HYAL; (G5) Cells + HA-HMW + hydroxyapatite; (G6) Cells + HA-LMW + hydroxyapatite; (G7) Cells + HA-HMW + HYAL + hydroxyapatite; (G8) Cells + HA-LMW + HYAL + hydroxyapatite; (G9) Cells (positive control); (G10) Cells + hypochlorite (negative control). The cell viability for each group were as follows: (G1) 76,0%, (G2) 63,3%, (G3) 67,4%, (G4) 76,5%, (G5) 57,6%, (G6) 60,8%, (G7) 64,4%, (G8) 74,3%, (G9) 100% e (G10) 12,4%. It was found that all groups had significantly higher cell viability compared to the negative control. And although there was no significant difference between experimental groups, only the G1, G4 and G8 groups did not differ significantly from the positive control. Therefore, HA-HMW had better viability in the absence of enzyme hyaluronidase, although HA-LMW provided greater cell viability in the presence of the enzyme. Results indicated that the low-weight hyaluronic acid might be applicable for tissue engineering grafting techniques.